Effect of Origin and Ownership Status on Beef Cattle Reproductive Performance and Development Strategies in Sekolah Peternakan Rakyat (SPR) - Dinda Ayu Permata Sari; Muladno; Syahruddin Said; Nahrowi; Rudy Priyanto (UNIVERSITAS ISLAM LAMONGAN, 2025)
This study aims to determine the effect of cattle origin and ownership status on the reproductive performance of beef cows in four locations of the Sekolah Peternakan Rakyat (SPR). The study locations include SPR Sungai Lilin (Musi Banyuasin Regency), Mesuji Raya (Ogan Komering Ilir Regency), Pelepat Ilir (Bungo Regency) and Wanaraya (Barito Kuala Regency). The study was conducted through a survey method with direct observation and interviews with SPR members. The variables observed included age at first calving, calving interval, empty period, and service per conception (S/C). The factors analyzed were cattle origin (within or outside the SPR) and ownership status (personal or profit-sharing). The results showed that cattle origin had no significant effect on AFC, CI, DO and S/C. Ownership status had a significant effect on AFC, CI and DO. Recommendation of reproductive optimization strategies based on livestock origin include strengthening breeding stock, standardization of the quality of parents, both from within and outside the SPR area and certification of cattle origin, In contrast, reproductive optimization strategies based on ownership status include reformulation of the profit-sharing model, incentive programs for profit-sharing farmers, development of a gradual ownership scheme.